Micropathological Chip Modeling the Neurovascular Unit Response to Inflammatory Bone Condition. Issue 11 (25th February 2022) - Neto, Estrela; Monteiro, Ana Carolina; Leite Pereira, Catarina; Simões, Miguel; Conde, João Pedro; Chu, Virginia; Sarmento, Bruno; Lamghari, Meriem
Abstract: Organ‐on‐a‐chip in vitro platforms accurately mimic complex microenvironments offering the ability to recapitulate and dissect mechanisms of physiological and pathological settings, revealing their major importance to develop new therapeutic targets. Bone diseases, such as osteoarthritis, are extremely complex, comprising of the action of inflammatory mediators leading to unbalanced bone homeostasis and de‐regulation of sensory innervation and angiogenesis. Although there are models to mimic bone vascularization or innervation, in vitro platforms merging the complexity of bone, vasculature, innervation, and inflammation are missing. Therefore, in this study a microfluidic‐based neuro‐vascularized bone chip (NVB chip) is proposed to 1) model the mechanistic interactions between innervation and angiogenesis in the inflammatory bone niche, and 2) explore, as a screening tool, novel strategies targeting inflammatory diseases, using a nano‐based drug delivery system. It is possible to set the design of the platform and achieve the optimized conditions to address the neurovascular network under inflammation. Moreover, this system is validated by delivering anti‐inflammatory drug‐loaded nanoparticles to counteract the neuronal growth associated with pain perception. This reliable in vitro tool will allow understanding the bone neurovascular system, enlightening novel mechanisms behind the inflammatory bone diseases, bone destruction, and pain opening new avenues for new therapies discovery. Abstract : A microfluidic‐based platform (neuro‐vascular bone chip) is developed to mimic the interaction between bone, endothelial, and neuronal cells. It has the potential to provide new insights into the poorly known crosstalk between innervation, angiogenesis, and bone in a pro‐inflammatory setting, and to be applied as reliable and biologically relevant model, to screen potential novel treatments targeting bone inflammation and pain.